Post-Regulatory Performance: Does Indonesia’s New Fiscal Law Strengthen Local Government Revenue? - Permata Sari, Tini; Sasti Ferina, Ika; Pasla, Bambang Niko Pasla (Jurnal Prajaiswara, 2025)
This study aims to analyze the effectiveness and contribution of local taxes and service charges to the locally generated revenue (PAD) of Palembang City, Ogan Ilir Regency, and Banyuasin Regency following the enactment of Law No. 1 of 2022 on Fiscal Relations between the Central and Regional Governments (UU HKPD). Background Problems: Despite their strategic role in fiscal decentralization, many regions in Indonesia, including South Sumatra, remain highly dependent on central transfers. Empirical studies on the actual impact of the new law at the local level are still limited. Research Methods: This study employs a descriptive quantitative method using 2024 data consisting of local tax revenue realization reports and regional budget revenue and expenditure realization reports obtained from the Regional Revenue Agency and the Regional Financial and Asset Management Agency of each respective region. Finding/Results: The study finds local taxes in Palembang City very effective and service charges effective; in Ogan Ilir, taxes are moderately effective but charges ineffective; Banyuasin shows effectiveness in both. However, their contribution to PAD remains minimal across all regions. Conclusion: Adjusting tax, retribution, and PAD targets based on the previous year’s realization is essential. Ogan Ilir and Banyuasin Regencies must align with regulatory developments to improve transparency and accountability, while Palembang City should optimize high-potential local tax collection and enhance retribution management through inter-agency supervision and coordination.